THE ELECTRONIC IRON CURTAIN AND VIRTUAL DEMOCRACY: LESSONS FOR UZBEKISTAN - TOLIPOV, Farkhad (CENTRAL ASIA AND THE CAUCASUS, 2012)
At the beginning of July 2012, the media and Internet reported that a documentary film shown on Uzbekistan’s Eshlar TV channel had compared social networks (in particular Facebook and Odnoklassniki) to machine guns and nuclear bombs. Social networks were also likened to weapons in the hands of the enemy. During the program, an expert from the Spirituality and Enlightenment Center asked the following question: “What is the difference between a terrorist and a blogger’s page on a social network showing photographs of naked people?” He also noted that “if terrorists kill people using weapons and bombs, Internet users are ultimately being killed with the aid of ‘sweet words;’ this kind of mass culture poses a direct danger to our state policy and our sovereignty.” Another expert accused Facebook and Odnoklassniki of propagandizing sexual perversion and “the extravagances of Western democracy.” The film called on young people to use local analogues of these websites instead—Muloqot.uz and Sinfdosh.uz.